Proceedings of the Proceedings of the 5th Annual International Seminar on Trends in Science and Science Education, AISTSSE 2018 2019
DOI: 10.4108/eai.18-10-2018.2287442
|View full text |Cite
|
Sign up to set email alerts
|

The Applying of the VAK Method in Improving Learning Outcomes in Basketball Dribbling on Physical Education, Health and Recreation Students Faculty of Sport Science, State University of Medan

Abstract: This study was aims to know increasing the results of learning basketball dribbling through the application of the V.A.K (visual, auditory, kinesthetic) method. It was conducted by using Classroom Action Research (CAR). It was conducted in two cycles. Subject of the study were the students of III semester B Class, it were 30 students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on the problems faced in the class, the solution that can solve these problems is to apply the visual, auditory, kinesthetic learning model (VAK) which is expected to be used by teachers in helping students to accommodate the three learning styles possessed by students so that students can also provide direct learning experience to students so as to improve the process and learning outcomes. Several studies have revealed that VAK learning has an impact on learning outcomes (Chairad et al, 2019;Khoirunnisa & Iba, 2022;Sary et al, 2020). The VAK learning model is a learning model that involves students' learning styles and makes use of all the sensory devices that students have which is carried out with activities that involve students directly to practice or are directly involved in conducting experiments (Ikawati & Kowiyah, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the problems faced in the class, the solution that can solve these problems is to apply the visual, auditory, kinesthetic learning model (VAK) which is expected to be used by teachers in helping students to accommodate the three learning styles possessed by students so that students can also provide direct learning experience to students so as to improve the process and learning outcomes. Several studies have revealed that VAK learning has an impact on learning outcomes (Chairad et al, 2019;Khoirunnisa & Iba, 2022;Sary et al, 2020). The VAK learning model is a learning model that involves students' learning styles and makes use of all the sensory devices that students have which is carried out with activities that involve students directly to practice or are directly involved in conducting experiments (Ikawati & Kowiyah, 2021).…”
Section: Introductionmentioning
confidence: 99%